Pencegahan Hewan Berbisa (Lipan) Dengan Memanfaatkan Cuka Dan Garam - Lestari, Widia; Ikhsani, Muhammad Zaky; Fani, Alifah Nurul; A, Annisa; Ulfah, Aushaf; Sepriani, Dian Try; Bahira, Hafiza; Tarigan, Irene Novita Sari; Hamdan, Lavisha Guseyvia; L, Lufina; Anggita L, Vidi Mayumi (Yayasan Daarul Huda Kruengmane, 2024)
Agrowisata Sub-district in Pekanbaru is a high-humidity area that supports the presence of venomous creatures, particularly centipedes. Centipede bites can cause pain, swelling, and infection risks, necessitating eco-friendly and cost-effective prevention solutions. This study aims to evaluate the effectiveness of vinegar and salt solutions as centipede repellents. Vinegar's acetic acid content disrupts centipede respiratory systems, while salt inhibits their movement and activity. Community education was conducted to introduce the preparation and application of this solution. Results indicated that vinegar and salt solutions effectively reduced centipede presence in residential areas. Furthermore, the community responded positively to this method due to its ease of implementation and safety. These findings are expected to serve as a reference for developing natural prevention approaches for venomous creatures in residential areas.